Mapping the Chemodynamics of the Galactic Disk Using the LAMOST and APOGEE Red Clump Stars - Sun, Weixiang; Shen, Han; Jiang, Biwei; Liu, Xiaowei (The Astrophysical journal. Supplement series, 2024)
A detailed measurement is made of the metallicity distributions, kinematics, and dynamics of the thin and thick disks across a large disk volume (5.0 ≤ R ≤ 15.0 kpc and ∣ Z ∣ ≤ 3.0 kpc) by using the LAMOST–APOGEE red clump stars. The metallicity distribution results show that the radial metallicity gradient Δ[Fe/H]/Δ R of the thin disk weakens with ∣ Z ∣ from −0.06 dex kpc −1 at around ∣ Z ∣ < 0.25 kpc to −0.02 dex kpc −1 at around ∣ Z ∣ > 2.75 kpc, while the thick disk displays a global weak positive Δ[Fe/H]/Δ R that is generally weaker than 0.01 dex kpc −1 . The vertical metallicity gradient Δ[Fe/H]/Δ∣ Z ∣ steadily weakened from −0.36 dex kpc −1 at R ∼ 5.5 kpc to −0.05 dex kpc −1 at around R > 11.5 kpc for the thin disk, while the thick disk presents an almost constant value (nearly −0.06∼−0.08 dex kpc −1 ) for all the R bins. These results indicate the contribution of the radial migration to the disk evolution, and the obvious north–south asymmetry in [Fe/H] may be linked to disk warp and/or disk perturbation events. The oscillations in the corrected Δ[Fe/H]/Δ∣ Z ∣ with R likely arise from the resonances with the Galactic bar. Our detailed measurements of Δ V ϕ /Δ[Fe/H] indicate an inside-out and upside-down star formation scenario for the thick disk. The results of eccentricity distributions and [ α /Fe]–velocity dispersion relations are likely to suggest that thick-disk stars require an obvious contribution from other heating mechanisms, such as mergers and accretion, or are born in the chaotic mergers of gas-rich systems and/or the turbulent interstellar medium.